2012
DOI: 10.3748/wjg.v18.i39.5608
|View full text |Cite
|
Sign up to set email alerts
|

Colonic stentingvsemergent surgery for acute left-sided malignant colonic obstruction: A systematic review and meta-analysis

Abstract: SEMS is not obviously more advantageous than emergent surgery for patients with acute left-sided malignant colonic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
3
21
0
1
Order By: Relevance
“…The incidence of anastomotic leak, as reported elsewhere [15, 17, 25], did not show statistical difference between SBTS and ES.…”
Section: Discussionsupporting
confidence: 60%
“…The incidence of anastomotic leak, as reported elsewhere [15, 17, 25], did not show statistical difference between SBTS and ES.…”
Section: Discussionsupporting
confidence: 60%
“…A prospective, randomized trial analyzed on an intention-to-treat basis failed to demonstrate that preoperative SEMS use for patients with left colon-cancer obstruction decreased the need for stoma placement because SEMS insertion was technically successful in only 47% of the patients [10]. Therefore, a preoperative SEMS procedure does not clearly have more advantageous outcomes than emergency surgery [2021]. However, a recent randomized trial with a 70% successful stenting rate found that SEMS insertion followed by interval elective surgery may be safer than emergency surgery, with a trend towards lower morbidity and mortality [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is the explanation for the restrictive and decreasing use over time of SEMS. Recent meta-analyses of trials comparing SEMS as bridge to surgery and emergency surgery confirmed the higher primary anastomoses and initial lower stoma rates after SEMS, but did not demonstrate a significant difference in mortality and morbidity between the 2 approaches [14,15]. Insufficient data on long-term survival are available from the randomized trials and do not allow for definitive conclusions [16,17].…”
Section: Discussionmentioning
confidence: 99%